ELEKTRON TA’LIM RESURSLARI VOSITASIDA AXBOROT TEXNOLOGIYALARINI KASBIY FAOLIYATGA YО‘NALTIRIB О‘QITISH METODIKASI - Allambergenova, M.X. (SCIENCE and SOCIETY, 2024)
This article discusses the creation of electronic learning resources and its didactic significance and teaching methodology today.
Keywords: electronic resources; information technology; professional activities; electronic aids; video lessons; didactic tools; methodology